An analysis of the interplay between marital relationships and mental health (2019)
Marriage is an institution that has played prominent roles in the history of humanity. It has aided the growth of the human race and also filled the vacuum of solitariness by creating companionship. This study discusses this important human institution from the perspective of mental health. Mental health, as applied in this study, is not referring to the presence of mental diseases, but the absence of it. This study examines marriage, by exploring the bilateral nexus between marriage and mental health via empiricism, which attributes experience as the origin and the source of validity of all possible knowledge. This is done with a view to analysing the place of marriage in emotional wellbeing and the psychological issues that can affect marriage.